2003
DOI: 10.1213/01.ane.0000066357.63011.75
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Mixing Lidocaine with Propofol on the Dose of Propofol Required for Induction of Anesthesia

Abstract: Adding lidocaine to propofol destabilizes the propofol emulsion. A randomized double-blinded trial found no statistically significant difference in the doses of propofol required for the induction of anesthesia whether administered as a freshly prepared propofol 1%/lidocaine 1% 10:1 mixture or as a separate injection after a dose of lidocaine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
1
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 21 publications
1
8
1
1
Order By: Relevance
“…Similar to our findings, two other studies suggested decreased anesthetic potency of propofol when administered as lidocaine mixed with propofol in rats [27] and women [10]. In contrast to our finding, two studies showed clinically insignificant effects in the study ranged from 200 : 10 to 200 : 50 propofol/lidocaine mg ratio [28] and 10 : 1 propofol 1%/lodocaine1% volume ratio [29]. …”
Section: Discussionsupporting
confidence: 85%
“…Similar to our findings, two other studies suggested decreased anesthetic potency of propofol when administered as lidocaine mixed with propofol in rats [27] and women [10]. In contrast to our finding, two studies showed clinically insignificant effects in the study ranged from 200 : 10 to 200 : 50 propofol/lidocaine mg ratio [28] and 10 : 1 propofol 1%/lodocaine1% volume ratio [29]. …”
Section: Discussionsupporting
confidence: 85%
“…Besides, the analgesic effect of lidocaine on propofol injections not only based on its local anesthetic effect but also on the decrease in pH of the propofol when given as a lidocaine mixture. Tan LH et al, compared the effects of propofol-lidocaine mixture and lidocaine pretreatment in adults on propofol injection pain and the dose of propofol required for the induction of anesthesia 18. They showed no statistically difference between the groups for propofol induced pain and induction dose of propofol like in our study.…”
Section: Discussioncontrasting
confidence: 44%
“…Six agent mixtures with corresponding control mixtures were prepared, as shown in Table 1. The volume of each agent mixed with propofol formulations was determined based on the amounts that had been shown to be effective in reducing propofol‐induced pain in previous studies [13, 14, 16–18, 22].…”
Section: Methodsmentioning
confidence: 99%